A highly antibacterial achievement of hollow fiber polyethersulfone (PES) membrane loaded with silver nanoparticles - Fachrul Razi; Isao Sawada; Hideto Matsuyama (Syiah Kuala University, 2013)
A highly antibacterial of hollow fiber polyethersulfone (PES) membrane was prepared by loading silver nanoparticles within the PES graft acrylamide (AAm)-membrane. The grafted layers of AAm were provided the matrix for silver nanoparticles (AgNPs) entrapment. The characterization of the prepared hollowfiber (HF) PES membrane loaded with silver nanoparticles were examined by using transmission electron microscopy (TEM). To examine the antibacterial property of the prepared AgNPs-AAm-PES membrane, the halo zone and the shaking flask test were carried out. In these tests, both of unmodified PES membrane and AgNPs-AAm-PES membrane were exposed to pure culture suspension of Escherichia coli (E. Coli) bacteria with the concentration of 107 CFU/ml. The viable bacteria formed within the membrane surfaces and themembrane circumferences were observed by the halo zone formation, while the percentage of bacteria killing ratio was determined by shaking flask test method. The TEM results showed that the silver nanoparticles were formed within grafted layers of AAm-PES membrane and the size of silver nanoparticleswere about 10 nm. The AgNPs-AAm-PES membrane were highly effective to prevent the membrane biofouling as shown by the clearly halo zone formation compared with the unmodified PES membrane. The shake flask test were also revealed that almost 99.9 percent of the E. coli bacteria were killed when theyhaving exposed to the AgNPs-AAm-PES membrane. This was due to the silver ions are allowed to release from its membrane surface